Concentration in International Markets: Evidence from US Imports - Alessandra Bonfiglioli; Rosario Crinò; Gino Gancia (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We use transaction-level data to study changes in the concentration of US imports. Concentration has fallen in the typical industry, while it is stable by industry and origin country. The fall in concentration is driven by the extensive margin: the number of exporting firms has grown, and the number of exported products has fallen relatively more for top firms. Instead, average revenue per product of top firms has increased. At the industry level, top firms are converging, but top firms within country are diverging. Finally, higher concentration from an origin country is associated with a fall in prices, foreign entry and industry growth. These facts suggest that intensified competition in international markets coexists with growing concentration among national producers.
Keywords: E23; F12; F14; L11; R12; 330; superstar firms; concentration; US imports; firm heterogeneity; international trade